A Prediction of Waste Mobiles using Holt Trends Exponential Model - Swapnali Lotlikar, Dr. Ajay Khunteta, Dr. Mahesh Naik (International Journal of Modern Agriculture, 2021)
The use of cell phones (smart phones) is quickly increasing at a great rate and correspondingly the e-waste produce from mobile is due to their short life spans. One of the factors for shorter life spans of mobile is the rapidly changing technology. In competitive mobile phone market, manufacturers are forced to add new features periodically making relatively newer phone obsolete. To support new features new hardware like sensors are added to the mobile increasing their complexity. This rapid change in mobile technology brings environmental issues since users scrap their mobile phone in a short span of time. This paper predicts the number of e-waste generated through scrapped mobile by 2024 using time series model.